The fight against doping in Portugal in 1998 - Horta, L. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Portugal has an I.O.C. accredited Doping Laboratory since 1987 and ratified the European Convention against Doping of the Council of Europe in 1994. Its anti-doping policy is developed in three main fields: doping control, informative and educational campaigns and scientific investigation. In conclusion it can be stated that Portugal had a percentage of positive cases in accordance with the data obtained in other countries with strong policies against doping. The anti-doping policy should therefore be continued in high-risk modalities like Body building, Boxing and Weight-lifting and the number of controls performed in apparently low-risk modalities like motor sports, golf and roller-hockey should be increased to understand their real risk of doping abuse. In Soccer, the n umber of controls should be increased in the 3rd league and might be decreased in the 1st League. In 1999, a total of 3000 controls are expected, 15% of which out of competition.